Gut transcriptome analysis of P450 genes and cytochrome P450 reductase in three moth species feeding on gymnosperms or angiosperms - Zhang, Xiaoman; Shi, Zhiyong; Yang, Cai-qing; Li, Jing; Liu, Jingze; Zhang, Ai-bing (Frontiers in Ecology and Evolution, 2022)
Cytochrome P450 enzymes (P450s, CYPs) are a superfamily of heme-thiolate proteins involved in the metabolism of endogenous and exogenous substances in insects. In this study, identification of putative P450s proteins was done and elimination of the repeated sequences resulted in 57 proteins from Gastropacha populifolia, 63 proteins from Dendrolimus punctatus, and 53 proteins from Dendrolimus tabulaeformis. The putative P450s proteins were aligned together with seven other insect species based on five conserved domains. A total of ten co-orthologous groups were identified. Interestingly, one co-orthologous gene, CYP4g15 in CYP4 clan was identified and its 3D structure analysis showed that the highly conserved sites of the predicted motifs were close to the active sites of P450. Furthermore, this study revealed that insect CYP4g15 and two bacteria Cytochrome P450 were monophyletic. This suggests that insects CYP4g15 is not only functionally conserved but also an ancient gene originating from different bacteria species.